Diplomatic activities of M.M. Litvinov in the USA during the Great Patriotic War (1941–1943) - A. A. Vershinin; P. A. Tupikin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Great Patriotic War is one of the highlights in the history of Soviet-American cooperation. The USSR and the United States managed to overcome the inertia of mutual mistrust that persisted throughout most of the interwarperiod, taking together the lead in the fight against the Axis powers. However, rapprochement between the two future superpowers was neither plain nor swift; rather was it constantly hampered by mutual suspicion, aggravated by differences in their political cultures. Under these conditions, the fate of their alliance depended on the willingness of the ‘Big Three’ leaders to respect each other’s interest and concerns, as well as on the personal initiative and determination of individual politicians and diplomats. In this regard, the figure of M.M. Litvinov, appointed ambassador of the USSR to the United States at the most alarming and dangerous moment of the Great Patriotic War, deserves particular attention. Having played a major role in the Soviet-American cooperation in 1941–1943, M.M. Litvinov has been then forgotten for many years in both Soviet and Russian historiography. On the basis of new archive materials, the authors reexamine the activities of M.M. Litvinov as an ambassador to the United States and the specifics of his relationship with J.V. Stalin and V.M. Molotov during the period under review. The first section covers the initial steps of M.M. Litvinov in his new position. Special attention is paid to his efforts aimed at clarifying the Soviet position on the most sensitive issues of bilateral relations and establishing contacts with various groups of the American political, economic and intellectual elites. The second section analyzes M.M. Litvinov’s activities in the context of increasing contradictions between the Allies with regard to the opening of the second front and disruption of supplies under lend-lease. The authors show that M.M. Litvinov used all the diplomatic tools available to defend the interests of the USSR, instantly reacting to any changes in the moods of the U.S. military and political establishment and immediately reporting them to Moscow. In this context, the authors question the widespread claims in historiography about the ambassador’s excessive independence and willfulness. On the contrary, M.M. Litvinov can be said to have consistently adhered to the official foreign policy line of the Soviet leadership in both his speeches and practical steps. This indicates the need for further study of the M.M. Litvinov’s figure in order to avoid oversimplified, cliched assessments of this personality.